When Subjective Social Status Matters: Moderating Effects in the Association between Victimization and Mental Health - Antunes, Carla Rolo (Victims & offenders, 2021)
Social status is found to interfere with health outcomes after adverse life experiences. Evidence suggests the importance of subjective social status (SSS), above and beyond objective status. This study tests the moderating role of SSS in the association between victimization and mental health, considering the effect of distinct forms of victimization, clinical symptoms and psychological well-being. A sample of 300 adults completed self-reported questionnaires. Results revealed that greater psychological victimization was associated with lower self-acceptance and autonomy, and greater sexual victimization was associated with lower autonomy, particularly when participants reported lower SSS. Implications for intervention with victims are discussed.